Microphysical Analysis and Modeling of Amazonic Deep Convection - Basso, João Luiz Martins (2018)
Atmospheric moist convection is one of the main topics discussed on weather and climate. This study purpose is to understand why different and similar cloud microphysics parameterizations produce different patterns of precipitation at the ground through several numerical sensitivity tests with the WRF model in the simulation of a squall line case observed on the Amazon region. Four different bulk microphysics parameterizations (Lin, WSM6, Morrison, and Milbrandt) were tested, and the main results show that statistical errors do not change significantly among each other for the four numerical domains (from 27 km up to 1 km grids). The correlations between radar rainfall data and the simulated precipitation fields show the double-moment parameterization Morrison scheme was the one that displayed better results in the overall: While Morrison scheme show 0.6 correlation in the western box of the 1 km domain, WSM6 and Lin schemes show 0.39 and 0.05, respectively. Nevertheless, because this scheme presents good correlations with the radar rain rates, it also shows a fairly better system lifecycle, evolution, and propagation when compared to the satellite data. Although, the complexity that the way microphysics variables are treated in both one-moment and double-moment schemes in this case study do not highly affect the simulatios results, the tridimensional vertical cross-sections show that the Purdue Lin and Morrison schemes display more intense systems compared to WSM6 and Milbrandt schemes, which may be associated with the different treatments of the ice-phase microphysics. In the specific comparison between double-moment schemes, the ice quantities generated by both Morrison and Milbrandt schemes highly affected thesystem displacement and rainfall intensity. This also affects the vertical velocities intensity which, in its, turn, changes the size of the cold pools. Differences in ice quantities were responsible for distinct quantities of total precipitable water content, which is related with the verticallly integrated ice mixing ratio generated by Morrison. The system moves faster in Milbrandt scheme compared to Morrison because the scheme generated more graupel quantities, which is smaller in size than hail, and it evaporates easier in the processes inside the cloud due to its size. This fact also changed the more intense cold pools intensity for Milbrandt scheme compared to Morrison.